Analisis Metode Khusus dan Sumber Penafsiran pada Surat Al-Jumu’ah dalam Tafsir Fathul Qodir - Gunara, Yusman; Irsad, Nursalim; Sofyan, Muhammad; Zulaiha, Eni (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
This study analyzes the methods and sources of tafsir used in Tafsir Fathul Qodir by Imam Muhammad bin Ali bin Muhammad Ash-Shukani with a focus on the interpretation of Surah Al-Jumu'ah. This study aims to explore how specific tafsir methods, such as the Tahlili method, are applied in this tafsir in order to provide a deep and contextual understanding of the verses of the Qur'an. This research uses a qualitative approach based on literature study, by reviewing various primary and secondary sources. The results show that the work of Imam Muhammad bin Ali bin Muhammad Ash-Shukani combines the approach of tafsir Bil Ma'tsur (history-based) with Tafsir Bil Ra'yi (reason-based). Primary sources such as the Qur'an, hadith, and the opinions of the companions are used comprehensively, while linguistic analysis and grammatical rules strengthen the interpretation of the verse. The interpretation of Surat Al-Jumu'ah emphasizes lughawi and fiqh patterns, which can be seen from the detailed explanation of the language structure and the discussion related to worship commands, such as Friday prayers. This research contributes to the understanding of Qur'anic interpretation that is applicable and contextual, and highlights the importance of using methods and sources of interpretation in facing the challenges of modern life. Tafsir Fathul Qodir is an important reference in the study of Qur'anic interpretation, especially in understanding the relevance of the verses of Al-Jumu'ah in the social and spiritual life of Muslims.